Early detection of chronic asymptomatic chagas infection - de la Rosa, Ezequiel (2018)
Chagas disease, also known as American trypanosomiasis, is a chronic and systemic parasitic infection which has become a serious epidemiological problem not only in endemic regions (Latin America), but also in nonendemic ones like North America, Europe, and Oceania. Subjects with the indeterminate chagasic form (ICF), a chronic asymptomatic disease stage, are the main sources of non-vectorial dissemination through blood transfusion, organ transplantation, and congenital transmission. It has been suggested that 94% of urban infections can be explained by these subjects. Under this scenario, the availability of simple and effective screening methods for ICF detection becomes crucial for both prevention of disease propagation and detection of clinical stages. Recently, a new non-invasive method has been proposed for ICF detection. It is based on surface high-resolution ECG and it could be easily adopted and included in modern ECG devices, overcoming the limitations of serological-based tests. The proposed method shows accuracy for early ICF screening, thus improving prognosis by defining the clinical stages and allowing appropriate and effective treatment.